Trust and Law - García Inda, Andrés (DERECHOS Y LIBERTADES: Revista de Filosofía del Derecho y derechos humanos, 2022)
This article is part of the monographic section "Derecho y confianza”What is the relationship between Law and Trust? And how can the Law promote an “adequate” social trust? Tommaso Greco’s book on La legge della fiducia offers an answer to such questions and proposes a review of “legal machiavellianism”, understood as the classical legal paradigm, based on mistrust. In this work, from the reading of that book, some reflections are raised on the relationship about Law and Trust, and a critique of Greco’s “principled” approach is made.
Keywords: Law; trust; duties; principles; links